2016
DOI: 10.4314/ahs.v16i2.32
|View full text |Cite
|
Sign up to set email alerts
|

Factors associated with gastro-duodenal disease in patients undergoing upper GI endoscopy at the Korle-Bu Teaching Hospital, Accra, Ghana

Abstract: Background: There is a high prevalence of gastro-duodenal disease in sub-Saharan Africa. Peptic ulcer disease in dyspeptic patients, 24.5%, was comparable to prevalence of gastro-duodenal disease among symptomatic individuals in developed countries (12 -25%). Limited data exists regarding its associated risk factors despite accumulating evidence indicating that gastroduodenal disease is common in Ghana. Objectives: This study investigates risk factors associated with gastro-duodenal disease at the Korle-Bu Tea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
19
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(20 citation statements)
references
References 19 publications
1
19
0
Order By: Relevance
“…In addition, 66% of the patients indicated NSAID use, 89% alcohol intake of >5 units/d, 55.3% fasting or irregular eating and 61.9% were H. pylori positive . Another smaller study from Ghana provided similar results, that is, H. pylori being the leading risk factor for PUD, yet NSAID‐related injury being common in H. pylori infected individuals …”
Section: Helicobactor Pylori and Peptic Ulcer Diseasementioning
confidence: 81%
See 1 more Smart Citation
“…In addition, 66% of the patients indicated NSAID use, 89% alcohol intake of >5 units/d, 55.3% fasting or irregular eating and 61.9% were H. pylori positive . Another smaller study from Ghana provided similar results, that is, H. pylori being the leading risk factor for PUD, yet NSAID‐related injury being common in H. pylori infected individuals …”
Section: Helicobactor Pylori and Peptic Ulcer Diseasementioning
confidence: 81%
“…2 Another smaller study from Ghana provided similar results, that is, H. pylori being the leading risk factor for PUD, yet NSAID-related injury being common in H. pylori infected individuals. 3 The recurrence of PUD depending on the H. pylori status was analyzed in a retrospective multicentric study in Korea involving 1,761 patients. 4 As anticipated, the 5 year cumulative probability of PUD recurrence was high in the group which had not received eradication treatment (43.8%).…”
Section: Helicobactor Pylori and Peptic Ulcer Diseasementioning
confidence: 99%
“…For instance, a study on the prevalence of dyspepsia in rural Northeastern Nigeria demonstrated that over 50% of dyspeptic patients sought medical help mainly from traditional healers[2]. These observations and tendancies are thought to have resulted in the reported prevalence of peptic ulcer disease (PUD) and gastric cancer (GCA) in Africa being significantly lower than that in other areas of the world[3].…”
Section: Introductionmentioning
confidence: 99%
“…This subsequently leads to a variety of empirical therapies for symptomatic individuals further delaying definitive diagnosis, and thereby contributing to the observed low prevalence of GDD in some areas[1,5]. Following the increasing availability of flexible upper GI endoscopy over recent years, it has now become apparent that GDD is prevalent across the continent of Africa[1,3]. Currently, in Ghana, there are endoscopic services and CT scan facilities in tertiary medical centres but not at most regional or district hospitals.…”
Section: Introductionmentioning
confidence: 99%
“…29 The section concludes a much awaited paper from Gabon: Cerebrospinal meningeal infections in HIV-infected patients. 30 We have a paper on upper GIT endoscopy 31 , while the next set of papers is on herbal remedies. 32 …”
Section: Infections: Preventionmentioning
confidence: 99%